PREPARATION OF OSTEOPOROTIC WOMEN IN MENOPAUSE FOR DENTAL IMPLANTATION AND PREVENTION OF EARLY COMPLICATIONS - Pulatova Barno Zhurakhonovna; Achilova Nodira Ganievna; Bobamuratova Dilnoza Turdikulovna (Web of Journals Publishing, 2024)
Frequent referral of elderly patients, especially women, for removal of dental defects with the use of implants makes this problem especially important because asymptomatic, inconspicuous course of osteoporosis can be the cause of complications during treatment with the use of intraosseous implants.
Keywords: Osteoporosis, systemic osteoporosis, dental implantation, menopause Introduction According to the World Health Organization, one of the most important public health problems is osteoporosis, which ranks Fourt.